Implementation status of household contact tuberculosis screening by health extension workers: assessment findings from programme implementation in Tigray region, northern Ethiopia - Hailay Gebretnsae; Brhane Gebrekidan Ayele; Tsegay Hadgu; Esayas Haregot; Aregay Gebremedhin; Eyassu Michael; Mebrahtu Abraha; Daniel G. Datiko; Degue Jerene (BMC, 2020)
Abstract Background In the Tigray region of Ethiopia, Health Extension Workers (HEWs) conduct Tuberculosis (TB) screening for all household (HH) contacts. However, there is limited evidence on implementation status of HH contact TB screening by HEWs. The aim of this program assessment was to describe the implementation status and associated factors of HH contact TB screening by HEWs. Methods This programme assessment was conducted in three randomly selected districts from March to April 2018. Data was collected by using pre-tested structured questionnaire. Descriptive statistics was carried out using frequency tables. Logistic regression analysis was done to identify factors associated with HH contacts screening by HEWs. Results In this programme assessment a total of HHs of 411 index TB cases were included. One-fifth (21.7%) of index TB cases had at least one HH contact screened for TB by HEWs. Having TB treatment supporter (TTS) during intensive phase of index TB case (AOR = 2.55, 95% CI: 1.06-6.01), health education on TB to HH contacts by HEWs (AOR = 4.28, 95% CI: 2.04-9.00), HH visit by HEWs within 6 months prior to the programme assessment (AOR = 5.84, 95% CI: 2.81-12.17) and discussions about TB activities by HEWs with Women Development Army (WDA) leaders (AOR = 9.51, 95% CI: 1.49-60.75) were significantly associated with household contact TB screening by HEWs. Conclusions Our finding revealed that the proportion of HH contact TB screened by HEWs was low. Therefore, HEWs should routinely visit HHs of index TB cases and provide regular health education to improve contact screening practice. In addition, it is highly recommended to strengthen HEWs regular discussion about TB activities with WDA leaders and TB TTS.